2020
DOI: 10.1007/s00223-020-00679-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term rates of change in musculoskeletal aging and body composition: findings from the Health, Aging and Body Composition Study

Abstract: Musculoskeletal disorders are common among older people. Preventive strategies require understanding of age-related changes in strength, function and body composition, including how they interrelate. We have described, and examined associations between, 9-year changes in these parameters among 2917 Health, Aging and Body Composition Study participants (aged 70-79 years). Appendicular lean mass (ALM), whole body fat mass and total hip BMD were ascertained using DXA; muscle strength by grip dynamometry; and musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
2
20
0
1
Order By: Relevance
“…Total kilocalories expended per week was calculated by multiplying the participant's weight (kg) by the sum of the caloric expenditure for all activities performed, as previously described [ 17 ]. As in previous analyses [ 18 , 19 ], the number of self-reported comorbidities (ever told by a doctor) was used as a marker of comorbidity out of the following: stroke, diabetes, Parkinson’s disease, chronic obstructive pulmonary disease, heart attack or myocardial infarction, congestive heart failure and hypertension. Cognitive function was measured using the Modified Mini-Mental State Examination (3MS) with scores ranging from 0 to 100 (higher scores indicate better function) [ 20 ]; scores were dichotomized for analysis; and participants with scores < 80 were regarded as having low cognitive function [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total kilocalories expended per week was calculated by multiplying the participant's weight (kg) by the sum of the caloric expenditure for all activities performed, as previously described [ 17 ]. As in previous analyses [ 18 , 19 ], the number of self-reported comorbidities (ever told by a doctor) was used as a marker of comorbidity out of the following: stroke, diabetes, Parkinson’s disease, chronic obstructive pulmonary disease, heart attack or myocardial infarction, congestive heart failure and hypertension. Cognitive function was measured using the Modified Mini-Mental State Examination (3MS) with scores ranging from 0 to 100 (higher scores indicate better function) [ 20 ]; scores were dichotomized for analysis; and participants with scores < 80 were regarded as having low cognitive function [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the context of Covid-19, the physical deterioration, prevalent comorbidities, and the potential psychological effects generally place the elderly population at increased risk of accidental events, including cerebrovascular disease (stroke and transient cerebral haemorrhage). In addition, there is an increased concern that the elderly might be at a higher risk of falls and related fractures, due to the more prevalent osteopenia and osteoporosis with aging [4,5]. These accidental events not only increase the consumption of medical resources that have been already scarce but also make the sustainers susceptible to or infected with COVID-19 via the way of transmission in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline data showed that the age Group II patients were less than the corresponding value of Group I, indicating that the osteoporotic process is accelerated in Group II. Ageing is a signi icant risk factor for the decline in the BMD of the total hip (Westbury et al, 2020). The percentage of current smokers among Group II is signi icantly higher than the corresponding percentage of the Group I patients, indicating that smoking is a confounding risk factor of osteoporosis among Group II patients.…”
Section: Discussionmentioning
confidence: 91%